The Public Spaces in the Historical City: Characteristics and Transformations: Case Study; the Ksar of Khanguet Sidi Nadji, Algeria - Ghanemi , Faten; Makhloufi, Soumaya; Meliouh , Fouzia; Hamel , Khalissa; Nasri , Manel (Indonesian Journal of Social Science Research, 2024)
This article examines the evolution of the morphological characteristics of the square as an urban public space within the historical Algerian city, focusing particularly on the case of the Ksar of Khanguet Sidi Nadji, a small town situated between Biskra and Khanchela at the foot of Djebel Chechar and on the edge of the eastern Zab. The study aims to analyze the impact of urban transformations on the morphological characteristics of the square over time, focusing particularly on the topological, geometric, and dimensional relationships. In doing so, it considers the historical context and the changes that the Ksar has undergone over time. To achieve this, a dual methodology was adopted, combining two integrated approaches. Firstly, the historical method was employed to study the original morphological characteristics of the square by relying on historical documents, particularly through the analysis of texts by travellers during the late nineteenth and early twentieth centuries. Secondly, typo-morphology was applied to analyze the current urban configuration of the square and extract its current morphological characteristics, while a comparative approach highlighted the various transformations it has undergone. The results reveal that despite its marginal presence in the traditional urban fabric, the morphological characteristics of the square remain closely linked to its original function as a public space. Urban developments have certainly altered its configuration, but its fundamental features such as the arrangement of buildings around the square, access points, and meeting places remain related to its initial role.